Investigation of ErbB-2 Overexpression on Patients with Gastric Cancer in Eastern Anatolia of Turkey - Habib EMRE; Salim Başol TEKİN and Hasan DOĞAN and Kerim ÇAYIR and Mehmet BİLİCİ and; ŞİPAL and İbrahim PİRİM (Turkish Journal of Gastroenterology, 2019)
-